2013
DOI: 10.3389/fpls.2013.00037
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium graminearum and Its Interactions with Cereal Heads: Studies in the Proteomics Era

Abstract: The ascomycete fungal pathogen Fusarium graminearum (teleomorph stage: Gibberella zeae) is the causal agent of Fusarium head blight in wheat and barley. This disease leads to significant losses of crop yield, and especially quality through the contamination by diverse fungal mycotoxins, which constitute a significant threat to the health of humans and animals. In recent years, high-throughput proteomics, aiming at identifying a broad spectrum of proteins with a potential role in the pathogenicity and host resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…To assess connections and discrepancies with previously published studies, we compared our results to three 2-DE works which have investigated the Fg /wheat interaction but under contrasting conditions (different wheat cultivars and Fg strains, other sampling points and different tissues) (Dornez et al 2010; Ding et al 2011; Yang et al 2013) (Fig. 3) (Table 4Sa, 4Sb and 5S).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess connections and discrepancies with previously published studies, we compared our results to three 2-DE works which have investigated the Fg /wheat interaction but under contrasting conditions (different wheat cultivars and Fg strains, other sampling points and different tissues) (Dornez et al 2010; Ding et al 2011; Yang et al 2013) (Fig. 3) (Table 4Sa, 4Sb and 5S).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies were primarily focused on understanding the genetic basis of major QTLs (e.g., fhb1). Proteomic studies pointed diverse mechanisms of resistance such as oxidative burst, oxidative stress, response and induction of PR proteins, changes in hormones and secondary metabolism in barley (Yang et al 2013) and in wheat (Hamzehzarghani et al 2005; Yang et al 2013). Another study combining proteomics and metabolomics approaches suggested that the fhb1 resistance is mainly associated with cell wall thickening due to deposition of hydroxycinnamic acid amides, phenolic glucosides and flavonoides, but not with the conversion of DON to less toxic DON 3-O-glucoside (Gunnaiah et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous approaches to control diseases caused by F. graminearum have been proposed, but epidemics continue worldwide (Pirgozliev et al ., ; Goswami and Kistler, ) and scientific and economic impacts remain high (Dean et al ., ). Identifying the molecular mechanisms that underlie pathogenicity, mycotoxin production and fungal development remain important goals to improve disease control strategies (Trail, ; Yang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…F. graminearum causes head blight (scab) of wheat, barley, corn and rice and is listed among the Top 10 fungal pathogens as threats to the world’s food supply [11]. Not only does infestation cause huge losses in grain production, the scabby grain is contaminated with trichothecene and estrogenic mycotoxins, making it unsuitable for food or feed [12, 13]. The F. graminearum gene of interest, designated here as Fg-cat, has the characteristics of a fatty acid hydroperoxide-metabolizing enzyme with the distal heme signature sequence of Thr-His [8].…”
Section: Introductionmentioning
confidence: 99%